Impact of Physical Activity Programs on Hypertension Management in Anjir Serapat Muara Village - Maulida, Wulan; Agustina, Anita; Sundari, Sundari; Ramlianor, Muhammad; Sugara, Robby Aditya Azhar; Effendi, Muhammad; Wasila, Hardi (UrbanGreen Central Media, 2025)
Hypertension is a condition in which a person experiences an increase in blood pressure above the normal limit, which is above 140/90 mmHg, which causes pain and even death. The purpose of this community service is to improve public health efforts through anti-hypertension exercises that can lower blood pressure in the community. The target of this community service activity is the community of Anjir Serapat Muara Village who suffer from hypertension with a total of 35 people. The method used in this community service is the lecture method and demonstration of gymnastics with the community. The results of this community service showed a decrease in systolic blood pressure of 17 mmHg and a decrease in diastolic blood pressure of 5 mmHg. Blood pressure evaluation was carried out 30 minutes after hypertension exercises were performed. This shows that hypertension exercises are effective in lowering blood pressure.